Chromatin-Remodeling Factor BRG1 Is a Negative Modulator of L. donovani in IFNγ Stimulated and Infected THP-1 Cells - Brar, Harsimran Kaur; Roy, Gargi; Kanojia, Akanksha; Madan, Evanka; Madhubala, Rentala; Muthuswami, Rohini (Frontiers in Cellular and Infection Microbiology, 2022)
Intracellular pathogens manipulate the host cell for their own survival by contributing to modifications of host epigenome, and thus, altering expression of genes involved in the pathogenesis. Both ATP-dependent chromatin remodeling complex and histone modifications has been shown to be involved in the activation of IFNγ responsive genes. Leishmania donovani is an intracellular pathogen that causes visceral leishmaniasis. The strategies employed by Leishmania donovani to modulate the host epigenome in order to overcome the host defense for their persistence has been worked out in this study. We show that L. donovani negatively affects BRG1, a catalytic subunit of mammalian SWI/SNF chromatin remodeling complex, to alter IFNγ induced host responses. We observed that L. donovani infection downregulates BRG1 expression both at transcript and protein levels in cells stimulated with IFNγ. We also observed a significant decrease in IFNγ responsive gene, Class II transactivator (CIITA), as well as its downstream genes, MHC-II (HLA-DR and HLA-DM). Also, the occupancy of BRG1 at CIITA promoters I and IV was disrupted. A reversal in CIITA expression and decreased parasite load was observed with BRG1 overexpression, thus, suggesting BRG1 is a potential negative regulator for the survival of intracellular parasites in an early phase of infection. We also observed a decrease in H3 acetylation at the promoters of CIITA, post parasite infection. Silencing of HDAC1, resulted in increased CIITA expression, and further decreased parasite load. Taken together, we suggest that intracellular parasites in an early phase of infection negatively regulates BRG1 by using host HDAC1 for its survival inside the host.